The Efficacy of the Malaysian Government’s Response Towards Cybercrime - Ahmad Redzuan Mohamad; Mohd Rizal Yaakop; Mohd 'Azmi Mohd Razif (Scientific Research Publishing Inc., 2025)
Open Journal of Political Science Volume: 14 No:1 (page: 166–176)